Efektivitas Penerapan Absensi Finger Print Dalam Meningkatkan Disiplin Pegawai Di Kantor Kelurahan Bintara Jaya - Syifa Aulia; Wahidin Septa Zahran; Yurisman Star (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The Effectiveness of Finger Print Attendance Implementation in Improving Employee Discipline at the Bintara Jaya Sub- District Office. Thesis of Public Administration Studies Program, Administrative Sciences Institute of Social Sciences and Management (Stiami). (Advised by Wahidin Septa Zahran, S.E, M.Si and Dr. Yurisman Star, S.E, M.Si). The purpose of this study was to analyze the effectiveness of the fingerprint attendance implementation in improving employee discipline at the Bintara Jaya Sub-District Office. The study was Qualitative research, which is a form of research that provides an overview by digging up data and facts in the field. The sources of the data were primary and secondary data. The data collection techniques were in the forms of observations, interviews and documentation with 8 informants. The results showed that the application of fingerprint attendance on 4 variables namely, target achievement, Adaptation, Satisfaction and responsibility had been effectively implemented at the Bintara Jaya Sub- District Office while the obstacles that occurred were power failures, bad internet network, and machine errors. The solution for undisciplined employees was by conducting a persuasive way to invite for discussion, give advice and motivation. Of course, it is hoped that the application of fingerprint attendance at this time can run well again in the future.